2019
DOI: 10.1186/s13068-019-1475-y
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency nuclear transformation of the microalgae Nannochloropsis oceanica using Tn5 Transposome for the generation of altered lipid accumulation phenotypes

Abstract: Background One of the major problems in the production of lipids for biotechnological purposes using microalgae is maintaining a high productivity of these molecules without reducing cellular biomass. High production rates are usually obtained by cultivating microalgae under different stress conditions. However, many of these changes usually result in lower biomass productivity. Therefore, the optimization of the culture conditions and genetic modification techniques in these organisms is needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…Nonetheless, EPA was found in significant high abundances in other microalgae, particularly in N. oceanica, which lacks ALA. In line with our results, previous studies reported a total absence of ALA and high abundances of EPA [77][78][79][80][81][82].…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, EPA was found in significant high abundances in other microalgae, particularly in N. oceanica, which lacks ALA. In line with our results, previous studies reported a total absence of ALA and high abundances of EPA [77][78][79][80][81][82].…”
Section: Discussionsupporting
confidence: 93%
“…Palmitic acid was the dominant constituent of SFAs, and showed signi cant changes upon culture treatment by tobacco smoke. It is known that palmitic acid is the most common component of the cell membrane and is the dominant SFAs [41]. Its signi cant changes in response to salinity stress have been reported previously [42,43], suggesting its possible role in acclimation to stress conditions.…”
Section: Effect Of Tobacco Smoke On Fatty Acid Pro Lementioning
confidence: 93%
“…By splicing HSP90 into a plasmid that codes for antibiotic resistance, the insertion of this plasmid can be tested by treating the host with antibiotics [33]. This is accomplished with a plasmid that contains the code for zeocin antibiotic resistance, pMOD-zeo, which will be ligated to the HSP90 HA plasmid using the restriction endonucleases NcoI-Styl and BseRI [34][35]. Using polymerase chain reaction (PCR) at 96°C, this mutant plasmid will be linearized to create free ends that can bind to T. suecica DNA.…”
Section: Methodsmentioning
confidence: 99%